Assessment of Leucocytes Migration Inhibition in Tuberculosis Patients - Khalid, T.S.; Al-Agidi, S. K.; Zuhair, W. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Leucocytes Migration Inhibition test in agarose was carried against PPD and Mycobacterium tuberculosisantigen . The proportion of different Kinds of migrating leucocytes was calculated and expressed as a function of the migration distance .            Application of this test to clinical problem revealed that with PPD as antigen , a highly significant inhibition was obtained in PPD skin test â€“ positive  normal  individual , as well as, a high significant inhibition was recorded in individuals recovered from tuberculosis .            These results demonstrated the suitability of this test for routine detection for cell mediated immunity